Anti-CD40 Antibody Fused to CD40 Ligand Is a Superagonist Platform for Adjuvant Intrinsic DC-Targeting Vaccines - Ceglia, Valentina; Zurawski, Sandra; Montes, Monica; Kroll, Mitchell; Bouteau, Aurélie; Wang, Zhiqing; Ellis, Jerome; Igyártó, Botond Z.; Lévy, Yves; Zurawski, Gerard (Frontiers in Immunology, 2022)
CD40 is a potent activating receptor expressed on antigen-presenting cells (APCs) of the immune system. CD40 regulates many aspects of B and T cell immunity via interaction with CD40L expressed on activated T cells. Targeting antigens to CD40 via agonistic anti-CD40 antibody fusions promotes both humoral and cellular immunity, but current anti-CD40 antibody-antigen vaccine prototypes require co- adjuvant administration for significant in vivo efficacy. This may be a consequence of dulling of anti-CD40 agonist activity via antigen fusion. We previously demonstrated that direct fusion of CD40L to anti-CD40 antibodies confers super agonist properties. Here we show that anti-CD40-CD40L-antigen fusion constructs retain strong agonist activity, particularly for activation of dendritic cells (DCs). Therefore, we tested anti-CD40-CD40L antibody fused to antigens for eliciting immune responses in vitro and in vivo. In PBMC cultures from HIV-1 infected donors, anti-CD40-CD40L fused to HIV-1 antigens preferentially expanded HIV-1-specific CD8+ T cells versus CD4+ T cells compared to analogous anti-CD40-antigen constructs. In normal donors, anti-CD40-CD40L-mediated delivery of Influenza M1 protein elicited M1-specific T cell expansion at lower doses compared to anti-CD40-mediated delivery. Also, on human myeloid-derived dendritic cells, anti-CD40-CD40L-melanoma gp100 peptide induced more sustained Class I antigen presentation compared to anti-CD40-gp100 peptide. In human CD40 transgenic mice, anti-CD40-CD40L-HIV-1 gp140 administered without adjuvant elicited superior antibody responses compared to anti-CD40-gp140 antigen without fused CD40L. In human CD40 mice, compared to the anti-CD40 vehicle, anti-CD40-CD40L delivery of Ea 52-68 peptide elicited proliferating of TCR I-Ea 52-68 CD4+ T cells producing cytokine IFNγ. Also, compared to controls, only anti-CD40-CD40L-Cyclin D1 vaccination of human CD40 mice reduced implanted EO771.LMB breast tumor cell growth. These data demonstrate that human CD40-CD40L antibody fused to antigens maintains highly agonistic activity and generates immune responses distinct from existing low agonist anti-CD40 targeting formats. These advantages were in vitro skewing responses towards CD8+ T cells, increased efficacy at low doses, and longevity of MHC Class I peptide display; and in mouse models, a more robust humoral response, more activated CD4+ T cells, and control of tumor growth. Thus, the anti-CD40-CD40L format offers an alternate DC-targeting platform with unique properties, including intrinsic adjuvant activity.